PENENTUAN KANDUNGAN LOGAM Pb DAN Cr PADA AIR DAN SEDIMEN DI SUNGAI AO DESA SAM SAM KABUPATEN TABANAN - DIANTARIANI, NI PUTU; DHARMA PUTRA, K.G. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Research on the heavy metal content, Pb and Cr in water and sediment of Ao River in Sam SamVillage, Tabanan Regency have been carried out. Sample of water taken at 8 location per week during 4weeks, while sample of sediment only taken once at 8 location. Determination of metal content of Pb and Crconducted using destruction method with mixture of HNO3 dan HCl (3:1) and analysed with AbsorptionAtomic Spectrophotometer.The result showed that mean metal content of Pb and Cr in water of Ao river at the location aftertextile industry (location 5 until 8) from four times intake of samples have passed enabled boundarythreshold that is 0,03 mg/L for Pb and 0,05 mg/L for Cr. Mean Pb content in sediment at location 1, 2, 3, 4and 5 still under natural content while location 6, 7 and 8 over the natural boundary threshold. Meanwhile forthe Cr metal only at location 8 over the natural boundary threshold. The highest metal content of Pb and Cr insediment and water found at location 8 that is each of 0,496 mg/L and 0,213 mg/L for Pb and Cr in water and141,844 mg/Kg and 33,489 mg/Kg for Pb and Cr in sediment respectively.